Comparative effectiveness of treatments for recurrent Clostridioides difficile infection: a network meta-analysis of randomized controlled trials - Duo, Hong; Yang, Yanwei; Zhang, Guqing; Chen, Yingxin; Cao, Yumeng; Luo, Linjie; Pan, Huaqin; Ye, Qifa (Frontiers in Pharmacology, 2024)
Background: Clostridioides difficile infection (CDI) is the most common cause of healthcare-associated infectious diarrhea. A major clinical challenge is recurrent CDI (rCDI) without effective standard drug-based therapy. Additionally, a comprehensive comparison of various therapy effectiveness in rCDI patients is still under investigation. Methods: A Bayesian network meta-analysis (NMA) of randomized control trials up to March 2024 was performed to investigate the efficacy of rCDI interventions. Results: Seventeen trials were included, comprising 4,148 CDI patients with ten interventions, including fecal microbiota transplantation (FMT) by lower gastrointestinal (LGI), FMT by upper gastrointestinal (UGI), Autologous FMT (AFMT), vancomycin + FMT, vancomycin, placebo, fidaxomicin, Vowst (SER109), Rebyota (RBX2660), and monoclonal antibody. NMA showed that FMT by LGI had the highest efficacy in treating rCDIs with an odds ratio (95% confidence interval) of 32.33(4.03, 248.69) compared with placebo. FMT by UGI also showed high efficacy, whereas the efficacy comparison between FMT by LGI and UGI was not statistically significant (ORs) (95% CI), 1.72 (0.65, 5.21). The rankogram and surface under the cumulative ranking curve (SUCRA) also showed FMT by LGI ranked at the top and FMT by UGI ranked second in the curative effect. Conclusion: NMA demonstrates FMT's significant efficacy in rCDI management, regardless of administration route (lower or upper gastrointestinal). Despite its significant benefits, FMT's safety is a concern due to the lack of standardized FDAcompliant manufacturing and oversight. Microbiota-based therapies also exhibit potential. However, limited research mandates further clinical exploration. Antibiotics, in contrast, display comparatively reduced efficacy in rCDI, potentially linked to disruptions in native gut microflora balance. Systematic Review: identifier CRD42022368435.